The Protective Effect of Solanum betaceum Extract on Spermatozoa Vitality Exposed to Lead Acetate in Mice - Rima Wirenviona; Reny I’tishom; Siti Khaerunnisa (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The purpose of this study was to analyze the effect of giving various dosages of Solanum betaceum extract on the vitality spermatozoa mice exposed to lead acetate. This research was true experimental using randomized post-test only control group design. The total sample was 40 mice which were divided into 5 groups. Lead acetate used a dose of 75 mg/kg BW and various extracts of Solanum betaceum namely 100 mg/kg BW, 200 mg/kg BW and 400 mg/kg BW. Acclimatization was carried out for 7 days and continued with maintenance and treatment for 35 days. Statistical tests showed that there was a significant difference with (p=0.026). In conclusion, Solanum betaceum extract can be used as a protective to increase the vitality of spermatozoa exposed to lead acetate